ASSESSMENT AND MANAGEMENT OF ASTHMA AND CHRONIC OBSTRUCTIVE PULMONORY DISEASE (COPD) – CONVERGING APPROACHES - Jones, Paul W (Journal of Postgraduate Medical Institute, 2011)
This review compares the methods of assessment and treatment objectives used for asthma and COPD. There is now a significant amount of convergence between the two diseases in these areas. It is now well recognised that both are inflammatory diseases. Anti-inflammatory therapy with inhaled corticosteroids (ICS) forms the basis of asthma therapy (and are underused in many countries, including Pakistan), but there also is now very good evidence that ICS reduce bronchial inflammation in COPD, especially when used in combination with long-acting beta -agonists. 2 Guidelines recommend that asthma assessment in routine practice, is based upon an evaluation of the level of asthma control; COPD assessment is moving towards something very similar, but it is termed health status measurement. Simple standardised methods designed for use in routine practice are now available for both purposes. Treatment in both conditions also now has two objectives: 1. To reduce symptoms to achieve control (in asthma) and improved health status (in COPD); 2. Preventative therapy to reduce the risk of exacerbations. In asthma, exacerbations are associated with a risk of hospital admissions and death and in COPD the same risks apply, but now with good evidence that exacerbations also speed disease progression. The treatments that are available for asthma can, if used properly, achieve high levels of control. Whilst new drugs are welcome, good application of existing drugs would very greatly reduce the burden of this disease on patients and healthcare systems. New treatments are steadily becoming available for COPD and there is now much that can be done to reduce the burden of this disease. Both diseases are eminently treatable.